Building A Web-Based Final Project Detection Information System with Incremental Method and Jaccard Similarity Algorithm - Maria Eryestin Nahak; Darsono Nababan; Yasinta O.L Rema (Department of Informatics, Universitas Islam Negeri Syarif Hidayatullah, 2023)
Thesis is a scientific work and one of the graduation requirements for students in tertiary institutions. The process of implementing the thesis at the Information Technology Study Program at the University of Timor is still done manually, starting from submitting titles to data processing which allows for duplicate titles, difficulty finding data and losing data. For this reason, a system is needed to avoid the risk of duplicate titles and difficulty finding the data. So in this study an information system will be built to detect the similarity of the title of the final project (Thesis) using the incremental method and the Jaccard similarity algorithm as a plagiarism detection algorithm. The application of the incremental method is due to its flexible nature and less risk of failure than other development methods. System testing is carried out on the functional system and using the User Acceptance Test. Based on the test results, this system facilitates Study Programs in submitting final assignment titles, finding final assignment data, minimizing the risk of duplicate titles through the Title Similarity Percentage testing feature to find out the highest level of similarity based on thesis title category and avoiding data loss.